Design, utilization, and analysis of simulations and game-based educational worlds - Ferdig, Richard E. (Premier Reference Source, 2013)
"This book presents developments and evaluations of games and computer-mediated simulations in order to showcase a better understanding of the role of electronic games in multiple studies" - Provided by publisher